Synalpheus pinkfloydi sp. nov., a new pistol shrimp from the tropical eastern Pacific (Decapoda: Alpheidae) - Anker, Arthur; Hultgren, Kristin M.; Grave, Sammy De (Zootaxa, 2017)
A new, conspicuously coloured species of the alpheid genus Synalpheus Spence Bate, 1888, is described based on material collected on the Pacific coast of Panama. Synalpheus pinkfloydi sp. nov. is closely related to the western Atlantic S. antillensis Coutière, 1909, the two taxa being transisthmian, cryptic sister species. Both species are characterised by the distal areas of their major and minor chelae coloured in an intense, almost glowing pink-red. The morphological differences between S. pinkfloydi sp. nov. and S. antillensis Coutière, 1909 are subtle, being limited to the slightly different proportions of the merus of both chelipeds, distodorsal armature of the major cheliped merus, relative length of the antennal scaphocerite, and body size. However, they are genetically different with a 10.2% sequence divergence in COI. Based on molecular clock estimates, these transisthmian taxa diverged around 6.8–7.8 mya, i.e. well before the final closure of the Isthmus of Panama 2.5–3 mya.